Systemic factors are trophic in bypassed rat small intestine in the absence of luminal contents. Issue 3 (March 1990) - Albert, V; Young, G P; Morton, C L; Robinson, P; Bhathal, P S
Abstract : Mucosal histology, crypt cell proliferation and brush border enzymes were measured in rats with varying degrees of jejunoileal bypass, in order to compare the effect of systemic and luminal factors on adaptive growth and differentiation (brush border enzymes) in small intestinal epithelium. Eighty five percent jejunoileal bypass caused a functional short gut; in intestine remaining in continuity there were significant increases in segmental weight, villus area and crypt depth, compared with sham operated controls and 25% jejunoileal bypass rats. Despite villus cell hyperplasia in 85% bypass rats, mucosal sucrase and alkaline phosphatase fell in jejunum and remained low in ileum, while leucine amino peptidase rose in ileum. There was a significant fall in villus area (p less than 0.01) and crypt cell production (p less than 0.001) in self emptying loops of 25% bypass rats not exposed to luminal contents compared with control segments of sham operated rats. In contrast, self emptying loops of 85% bypass rats were not atrophied despite the much greater distance from luminal nutrients; the villus area (p less than 0.01) and crypt cell production (p less than 0.005) were higher than in 25% bypass rats, and at least as great as in sham operated rats. These results indicate that adaptive hyperplasia has a variable effect on expression of brush border enzymes which might reflect villus cell immaturity. The atrophic effect of diversion of luminal contents can be counteracted by systemic growth factors released as part of the adaptive response; thus systemic growth factors are not dependent on a permissive effect of luminal contents.